Implementasi Pembinaan Profesionalisme Guru dalam Meningkatkan Kualitas Pembelajaran di MAN 1 Nganjuk - Moh Ali Fauzi; Prim Masrokan Mutohar; Rony Harsoyo (State Islamic Institute (IAIN) of Ponorogo, 2023)
The professionalism of teaching staff is very closely related to the quality of education, because the learning process as the core of education will depend heavily on professional teaching staff and the quality of learning outcomes is the spearhead of the quality of education. In this study the discussion will focus on the coaching carried out by the head of the Nganjuk MAN 1 madrasah in increasing teacher professionalism. It is hoped that with the development of professionalism for teachers, it can improve the quality of learning in a good class. The data collection technique used in writing this article is a qualitative approach with a descriptive research type. This article is reviewed with the hope that it will be able to provide comprehensive facts about the importance of fostering teacher professionalism in improving the quality of learning.